Acoustics of the one person space: headphone listening, detachable ambience, and the binaural prehistory of VR. Issue 1 (2nd January 2021) - Roquet, Paul
ABSTRACT: This article traces forgotten debates over the cultural acceptability of headphone listening in order to present an audio-centric history of private virtual space. I focus on how cultural attitudes towards headphone use transformed in tandem with developments in 3D binaural audio, new practices of solitary listening, and sound engineers' attempts to solve the "sound in the head" problem accompanying headphone use. Extending Jonathan Sterne's work on the "detachable echo" of modern sound mixing to what I call the detachable ambience of head-mounted spatial audio, I explore what happens when headphone listening eliminates the mediation of the surrounding physical space to create a solitary virtual acoustics. Examining the post-Walkman normalisation of headphone use, I argue it was only with the architectural emergence of what Nango Yoshikazu calls the "one person space" that headphone listening became acceptable as a personal media practice, setting the stage for more recent debates over the privatised three-dimensional space of the virtual reality head-mounted display.